Spatial modeling of Frankliniella occidentalis (Thysanoptera: Thripidae) on husk tomato using geostatistical techniques - Jiménez C., Rocio De Los Ángeles; Ramírez D., José Francisco; Sánchez P., Jesús Ricardo; Salgado S., Martha Lidya; Laguna C., Antonio (Revista Colombiana de Entomología, 2013)
The husk tomato (Physalis ixocarpa) is a food and medicinal crop of great economic importance in Mexico. However, it is affected by various pests and diseases, such as thrips and the viruses such as the of tomato spotted wilt virus (TSWV) causing up to 80% losses. The aim of this study was to model the spatial distribution of Frankliniella occidentalis using geostatistical techniques and obtain incidence maps by kriging. Were georeferenced 121 sampling points were georeferenced in each of the four commercial plots in the municipalities of Luvianos, Ixtlahuaca and Jocotitlán through the transect method on three phenological stages. The number of F. occidentalis in each sampling point was counted. Results showed that populations of F. occidentalis have an aggregated distribution, with several centers, viewed through the maps obtained. The semivariograms for the spatial distribution were adjusted mainly to Gaussian and spherical models. It was found that thrips infestation was not equally distributed in all the plots studied, which will establish strategies and control measures in terms of specific sites or point’s points of thrips infestation.